2016
DOI: 10.1038/srep23177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fitness traits and their plasticity on multiple plants for Sitobion avenae infected and cured of a secondary endosymbiont

Abstract: Regiella insecticola has been found to enhance the performance of host aphids on certain plants, but its functional role in adaptation of host aphids to plants is still controversial. Here we evaluate the impacts of R. insecticola infections on vital life-history traits of Sitobion avenae (Fabricius), and their underlying genetic variation and phenotypic plasticity on three plants. It was shown that effects of R. insecticola on S. avenae’s fitness (i.e., developmental time and fecundity) were neutral on oat or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 52 publications
4
33
0
Order By: Relevance
“…This was confirmed by the birth rates of the treatment groups, which were significantly lower than that of the controls. In conclusion, R. insecticola may reduce the potential growth of S. avenae clones, and this is consistent with the findings of Wang et al 27,. suggesting a possibility of a cost action to harbor this secondary endosymbiont.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This was confirmed by the birth rates of the treatment groups, which were significantly lower than that of the controls. In conclusion, R. insecticola may reduce the potential growth of S. avenae clones, and this is consistent with the findings of Wang et al 27,. suggesting a possibility of a cost action to harbor this secondary endosymbiont.…”
Section: Discussionsupporting
confidence: 93%
“…Wang et al 27. obtained the “curing of R. insecticola infected lines” through an oral administration of antibiotics, and they studied the change in the developmental time of 1 st to 4 th instar nymphs (DT1-DT4), the total developmental time of nymphs (DT5), and 10 d fecundity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and other studies reported negative fitness effects of this symbiont, for example, in the grain aphid, Sitobion avenae (Wang et al. ; Luo et al. ).…”
Section: Discussionmentioning
confidence: 85%
“…It's believed that facultative endosymbionts can enhance some biological and ecological traits for their host aphids, such as the frequency of sexual reproduction (Leonardo & Mondor, ; Simon et al, ), body coloration (Tsuchida et al, ), resistance to parasitoid wasps and pathogenic fungi (Oliver, Russell, Moran, & Hunter, ; Scarborough, Ferrari, & Godfray, ), and the capacity to withstand heat shock (Montllor, Maxmen, & Purcell, ; Russell & Moran, ). One of the most studied facultative symbionts in aphids is Hamiltonella defensa (Oliver et al, ; Vorburger, Gehrer, & Rodriguez, ; Wang et al, ). Some studies have shown that H. defensa can protect its host aphids (e.g., A. pisum and Aphis fabae ) against parasitoids to certain extents (Martinez, Weldon, & Oliver, ; Oliver et al, ; Schmid, Sieber, Zimmermann, & Vorburger, ; Vorburger et al, ), and the significance of its protective roles is dependent on specific H. defensa isolates and associated bacteriophage variants of APSE ( Acyrthosiphon pisum secondary endosymbiont; Degnan & Moran, ; Oliver, Degnan, Hunter, & Moran, ).…”
Section: Introductionmentioning
confidence: 99%